The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/apt.15133
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: the prevalence of small intestinal bacterial overgrowth in inflammatory bowel disease

Abstract: Background: Current data on small intestinal bacterial overgrowth (SIBO) in patients with inflammatory bowel diseases (IBD) are controversial.Aim: To conduct a systematic review and meta-analysis to determine the prevalence of SIBO in patients with ulcerative colitis (UC) and Crohn's disease (CD). Methods: Electronic databases were searched up to May 2018 for studies reporting prevalence of SIBO in IBD patients. The prevalence rate of SIBO among IBD patients and the odds ratio (OR) and 95% CI of SIBO in IBD pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
71
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 71 publications
3
71
1
4
Order By: Relevance
“…The high prevalence of SIBO observed can be explained, at least in part, by the fact that in CD, there are several predisposing factors for SIBO, such as surgery involving the gastrointestinal tract, especially ileocecal resection, dysmotility and stenoses or fistulas (14) . The rate of SIBO in this study is in agreement with that reported in other studies in patients with CD, ranging from 15% to 45% (3,(15)(16)(17)(18) , suggesting that SIBO is a common complication in patients with CD in various populations worldwide. Ricci et al (18) found an increased prevalence of SIBO in patients with CD compared to controls (32.6% vs 12.4%).…”
Section: Discussionsupporting
confidence: 92%
“…The high prevalence of SIBO observed can be explained, at least in part, by the fact that in CD, there are several predisposing factors for SIBO, such as surgery involving the gastrointestinal tract, especially ileocecal resection, dysmotility and stenoses or fistulas (14) . The rate of SIBO in this study is in agreement with that reported in other studies in patients with CD, ranging from 15% to 45% (3,(15)(16)(17)(18) , suggesting that SIBO is a common complication in patients with CD in various populations worldwide. Ricci et al (18) found an increased prevalence of SIBO in patients with CD compared to controls (32.6% vs 12.4%).…”
Section: Discussionsupporting
confidence: 92%
“…Our recent systematic reviews and meta‐analyses, found an increased prevalence of SIBO in IBS and IBD, 12 irrespective of the mode of SIBO diagnosis applying the established routine techniques. Traditionally, hydrogen production on breath testing has been linked to diarrhea, 11 however, in recent years there has been increasing interest in the association between methane positivity on breath testing and constipation 49 .…”
Section: Discussionmentioning
confidence: 95%
“…There is emerging evidence for a link between intestinal dysbiosis, including SIBO, and diseases such as IBS, 11 IBD 12 and chronic liver disease 13 . Many patients in these groups are likely to be on a PPI, often for management of unexplained gastrointestinal symptoms or overlapping conditions 36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of scientific evidence highlights the importance of the small intestine microbiome in normal human physiology and response to dietary interventions [2,3]. Alterations in the small intestine microbiome are implicated in a number of human disorders, such as malnutrition [4,5], obesity, and metabolic disease [6], inflammatory bowel disease (IBD) and irritable bowel syndrome (IBS) [7][8][9], and drug side effects [10]. Despite the apparent importance of the small intestine microbiome in human health, it remains understudied and poorly characterized largely because of the procedural and logistical complexities associated with its sampling in humans (methods are too invasive and require specialized healthcare facilities).…”
Section: Introductionmentioning
confidence: 99%